PENDAMPINGAN PENDAFTARAN PERSEROAN PERORANGAN BAGI USAHA MIKRO DAN KECIL PADA PERKUMPULAN PENYANDANG DISABILITAS INDONESIA - Dirkareshza, Rianda; Sadiawati, Diani; Novyana, Hilda; Sakti, Muthia; Agustanti, Rosalia Dika; Permatasari, Elizabet Devi; Hulu, Samuel Arthur; Falevi, Yunizar; Akhdan, Fariz Ridhanus; Marasabessy, Masita; Amanda, Nur Septiana (JCES (Journal of Character Education Society), 2023)
Abstrak: Adanya stigma negatif dan sulitnya akses informasi bagi penyandang disabilitas menyulitkan mereka untuk memperoleh pekerjaan ataupun membuat usaha sendiri. Untuk mengatasi masalah ini, pengabdian kepada masyarakat ini bertujuan untuk memberikan solusi agi penyandang disabilitas yang kurang mendapatkan informasi terkait pendaftaran perseroan perorangan sehingga mereka cinderung kesulitan untuk memperoleh izin atas usaha yang mereka miliki adanya pengabdian ini tentu dapat meningkatkan taraf hidup mereka terutama dalam aspek ekonomi dengan adanya izin yang jelas terkait usaha mereka sehingga mereka dapat menjalankan usahanya dengan lancar. yang dapat meningkatkan taraf hidup mereka terutama dalam aspek ekonomi . Pada kegiatan ini, menggunakan metode survei yaitu suatu penelitian yang dilakukan untuk memperoleh data-data dari fenomena yang berlangsung dan mencari keterangan-keterangan secara factual dari suatu kelompok. Kemudian dilanjutkan dengan analisis pendampingan pendaftaran perseroan perorangan bagi penyandang disabilitas. Hasil pengabdian kepada masyarakat menunjukkan bahwa adanya pendampingan dan pelatihan terkait pendaftaran perseroan perorangan memberikan pengetahuan dan juga keterampilan yang diperlukan untuk memberikan perlindungan dan kepastian hukum dalam menjalankan usaha. Kegiatan pendaftaran perseroan perorangan ini menghasilkan 3 (tiga) buah Sertifikat Nomor Induk Berusaha dan 9 (Sembilan) Sertifikat Pendaftaran Pendirian Perseroan.Abstract: The existence of negative stigma and difficult access to information for people with disabilities makes it difficult for them to get a job or create their own business. To overcome this problem, this community service aims to provide solutions for people with disabilities who lack information related to individual company registration so that they have difficulty obtaining permits for their businesses the existence of this service can certainly improve their living standards, especially in the economic aspect with a clear permit related to their business so that they can run their business smoothly. In this activity, using the survey method is a study conducted to obtain data from ongoing phenomena and seek factual information from a group. Then followed by the analysis of assistance for individual company registration for persons with disabilities as many as 13 people. The results of community service show that assistance and training related to the registration of individual companies provide the knowledge and skills needed to provide protection and legal certainty in running a business. This individual company registration activity resulted in 3 (three) certificates of business Identification Number and 9 (nine) certificates of registration of Company establishment. The existence of negative stigma and difficult access to information for people with disabilities makes it difficult for them to get a job or create their own business. To overcome this problem, this community service aims to provide solutions that can improve their standard of living, especially in the economic aspect. In this activity, using the survey method is a study conducted to obtain data from ongoing phenomena and seek factual information from a group. Then proceed with the analysis of the assistance of individual company registration for persons with disabilities. The results of community service show that the assistance and training related to the registration of individual companies provide the knowledge and skills needed to provide protection and legal certainty in running a business. This individual company registration activity resulted in 3 (three) certificates of business Identification Number and 9 (nine) certificates of registration of Company establishment.